Contribuições do grupo reflexivo como formação continuada em matemática de professores dos anos iniciais - Souza, Sandro Amorim de (2019)
This work aims to analyze the contributions of a Reflective Group for the continued education of teachers who teach Mathematics in the Early Years of Elementary School. To achieve this goal, we developed a qualitative research in four stages: in the first stage we performed a survey of the profile of teachers and the context investigated through a questionnaire; in the second stage we make observations of classes and semi-structured interviews; in the third and most important stage, we helped create the Reflective Group, a space for reflection and discussion about the pedagogical practices of the participating teachers, in which the data were collected; in the fourth step we analyzed and interpreted the data. The Reflective Group was constituted by 7 teachers from the municipal teaching network of the city of Santo Augusto - RS, who met in 10 weekly meetings with average over 76 minutes each. The audios of the meetings were transcribed in their entirety and the method of analysis was Moraes and Galiazzi's Discoursive Textual Analysis (DTA) (2007). The DTA allowed us to meet 437 units of meaning, their groupings generated 16 intermediate categories, which in turn were regrouped and formed three final categories: i) Challenges of the Teaching Practice; ii) Conceptions about Pedagogical Practices; iii) Constitution of the Reflective Group. This method of analysis allowed us to characterize significance and meanings related to the subject of our research, evidencing, through the reports of the participants, a clear evolution in the understanding of mathematical knowledge during the meetings of the Reflective Group, whether in statements directly related to these themes or in the ability to self-evaluate critically. In these situations, the self-criticism was directly related to the new conditions, obtained during the discussions promoted at the meetings, to evaluate more clearly the aspects to be potentialized or modified in their practices as teachers of Mathematics. The specific formation in the area occurred in a positive way and, according to their reports, is due to the exchange of information and experiences that occurred during the Reflective Group meetings, in which the participants simultaneously trained and received training. The positive aspects of our proposal were not only evident in the analysis carried out by the DTA, since the results of the interviews conducted before and after the Reflective Group, reaffirmed the changes in the way in which the participants began to evaluate their practices, allowing us to verify that the Reflective Group contributed to the continuing education of teachers who teach Mathematics in the Early Years.